Create your own webcomics with Webtoon : the ultimate guide to the exciting world of webcomics with tutorials, techniques, and insider tips! - Sosna-Spear, Quinn (Walter Foster, 2026)
"Unleash your creativity and dive into the world of webcomics with the tutorials, techniques, and insider tips in Create Your Own Webcomics with WEBTOON"-- Provided by publisher.